Differences in ultrasound features of papillations in unilocular‐solid adnexal cysts: a retrospective international multicenter study. (3rd August 2018) - Landolfo, C.; Valentin, L.; Franchi, D.; Van Holsbeke, C.; Fruscio, R.; Froyman, W.; Sladkevicius, P.; Kaijser, J.; Ameye, L.; Bourne, T.; Savelli, L.; Coosemans, A.; et al.
ABSTRACT: Objectives: To identify ultrasound features of papillations or of the cyst wall that can discriminate between benign and malignant unilocular‐solid cysts with papillations but no other solid components. Methods: From the International Ovarian Tumor Analysis (IOTA) database derived from seven ultrasound centers, we identified patients with an adnexal lesion described at ultrasonography as unilocular‐solid with papillations but no other solid components. All patients had undergone transvaginal ultrasound between 1999 and 2007 or 2009 and 2012, by an experienced examiner following the IOTA research protocol. Information on four ultrasound features of papillations had been collected prospectively. Information on a further seven ultrasound features was collected retrospectively from electronic or paper ultrasound images of good quality. The histological diagnosis of the surgically removed adnexal lesion was considered the gold standard. Results: Of 204 masses included, 131 (64.2%) were benign, 42 (20.6%) were borderline tumors, 30 (14.7%) were primary invasive tumors and one (0.5%) was a metastasis. Multivariate logistic regression analysis showed the following ultrasound features to be associated independently with malignancy: height of the largest papillation, presence of blood flow in papillations, papillation confluence or dissemination, and shadows behind papillations. Shadows decreased the odds of malignancy, while the other features increased them. Conclusion: We have identified ultrasound features that can help to discriminate between benign and malignant unilocular‐solid cysts with papillations but no other solid components. Our results need to be confirmed in prospective studies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 52: 157–158